Older Age and Worse Nutritional State Were Related with Impaired Inflammatory Response in Elderly Patients - Kuswardhani, Tuty; Sukrawan, Gede; Suastika, Ketut (BALI MEDICAL JOURNAL, 2016)
Background : Ageing process is related with multisystem disorders. One of them is immune response  impairment. It is imperative to evaluate the association between age and related nutritional status with  inflammatory response in elderly patient. Methods : A cross sectional study to evaluate inflammatory  response among elderly patients (?60 years) at Geriatric Out -patient Clinic, Sanglah Hospital was  conducted. Seventy-two patients were enrolled in the study. Age, nutritional states (body mass index  and mini nutritional assessment), and inflammatory markers (interleukin-2 [IL-2] and C-reactive  protein [CRP]) and other anthropometric as well as laboratory parameters were measured in the study.  Results : In the study it was revealed that age has a moderately negative correlation with both of  plasma IL-2 and serum CRP levels (R= -0.305, p=0.009; and R= -0.413, p=0.005, respectively).  Plasma IL-2 levels were positively correlated with several variables like body mass index (R=0.282,  p=0.016), mini nutritional assessment (R=0.237, p=0.045), biceps skin fold (R=0.291, p=0.013), and  triceps skin fold (R=0.258, p=0.028). While serum CRP levels has positive correlation with lying  diastolic blood pressure (R=0.345, p=0.020) and negative correlation with calf circumference (R=- 0.312, p=0.037). No significant associations were found between diabetes and hypertension with  inflammatory markers. Conclusion : This study concluded that older age and worse nutritional state  were related to worse inflammatory response in the elderly patients.
Keywords: elderly, nutritional state, inflammatory response